2014
DOI: 10.1007/s11999-014-3651-5
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome Impairs Thumb Opposition and Circumduction Motion

Abstract: Improving understanding of thumb pathokinematics associated with carpal tunnel syndrome may help clarify hand function impairment associated with the syndrome given the critical role of the thumb in dexterous manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…P < 0.05 was considered statistically significant. We estimated that a sample size of 16 participants per group would be required to achieve 80% power to detect a 10° difference in the aggregated angle for the two groups, assuming an overall standard deviation of 10°, similar to what was observed in a previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…P < 0.05 was considered statistically significant. We estimated that a sample size of 16 participants per group would be required to achieve 80% power to detect a 10° difference in the aggregated angle for the two groups, assuming an overall standard deviation of 10°, similar to what was observed in a previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 85%
“…There is only one report of the comparison of thumb pronation angle along the three-dimensionally moving bone axis between healthy subjects and CTS patients using an optical motion capture system [ 35 ]. However, the pronation angle in the CTS group decreased, but not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the authors conclude a series of three recently published articles on the effect of carpal tunnel syndrome on thumb kinematics [3][4][5]. Their publications provide new insight into the neuromuscular control of the thumb and the importance of a maintained sensorimotor innervation.…”
Section: Where Do We Need To Go?mentioning
confidence: 85%
“…Their publications provide new insight into the neuromuscular control of the thumb and the importance of a maintained sensorimotor innervation. In earlier reports, they found that carpal tunnel syndrome, the most common nerve entrapment treated by hand surgeons, reduces thumb motion and flexion/extension ability in the thumb joints [3]. In addition, they observe that carpal tunnel syndrome alters proprioceptive performance in reach and grasp functions [4], and adversely affects the fine motor skills required in precision pinch tasks [5].…”
Section: Where Do We Need To Go?mentioning
confidence: 97%
“…It is caused by compression of the median nerve at the wrist. Particularly in patients with severe CTS, it is known that the palmar abduction of the carpometacarpal (CM) joint is restricted (e.g., [19]). Since the opposition of the thumb is hindered, significant change in grasping posture of the hands is expected when their palmar abduction of the CM joint is limited.…”
Section: Introductionmentioning
confidence: 99%